The Effectiveness of Using Digital Comic Media in Improving Maharah Qira'ah of Junior Secondary Level Students - Arvianti, Najwa; Mutholib, Abdul (Kalamuna: Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2025)
Maharah Qira'ah is an important aspect of Arabic language learning in Madrasah Tsanawiyah. However, many students experience difficulties in understanding Arabic texts effectively. Therefore, this study aims to determine the effectiveness of using digital comic media in improving maharah qira'ah of seventh grade students with the subject matter "al-bait". This study used Pre-Experimental design with One-Group Pretest-Posttest Design model. The sample consisted of 15 students selected by purposive sampling. Data were analyzed using normality test, Paired Sample T-test, and N-Gain Score calculation. The results showed that the data were normally distributed with a pretest significance value of 0.342 and posttest of 0.136 (p > 0.05). T-test showed a significant difference between pretest and posttest (p = 0.000 < 0.05). The N-Gain Score value of 0.7684 shows an increase in maharah qira'ah ability in the high category. In conclusion, the use of digital comics is effective in improving students' maharah qira'ah. This study makes an important contribution to the development of innovative learning media that can increase students' interest and understanding in learning Arabic.